The Potential of Capsule Hotel Service in Semarang - Lemy, Diena Mutiara; Heidi, Elisabeth (E-Journal of Tourism; Volume 6 Number 2 (September 2019)DO - 10.24922/eot.v6i2.49944, 2019)
In the last seven years, hospitality and tourism industry becomes one of the world’s fastest-growing industries (Carter, 2018). The data for this proposal are gathered from primary data (direct observation and questionnaires) and secondary data (online publications). Capsule Hotel Service provides capsule rooms for guests to stay, as well as one-stop-culinary The purpose of this feasibility research study is to see whether this business is feasible or not by looking at the marketing aspect.